Circulating endothelial cells in acute ischaemic stroke - Nadar, Sunil K.; Lip, Gregory Y. H.; Lee, Kaeng W.; Blann, Andrew D. (Thrombosis and Haemostasis, 2005)
Increased numbers of CD146-bearing circulating endothelial cells (CECs) in the peripheral blood probably represent the most direct evidence of endothelial cell damage. As acute ischaemic strokes are associated with endothelial abnormalities, we hypothesised that these CECs are raised in acute stroke, and that they would correlate with the other indices of endothelial perturbation, i.e. plasma von Willebrand factor (vWf) and soluble E-selectin. We studied 29 hypertensive patients (19 male; mean age 63 years) who presented with an acute stroke and compared them with 30 high risk hypertensive patients (21 male; mean age 62 years) and 30 normotensive controls (16 male; mean age 58 years). CECs were estimated by CD146 immunobead capture, vWf and soluble E-selectin by ELISA. Patients with an acute ischaemic stroke had significantly higher numbers of CECs/ml of blood (p<0.001) plasma vWf (p=0.008) soluble E-selectin (p=0.002) and higher systolic blood pressure (SBP) as compared to the other groups. The number of CECs significantly correlated with soluble E-selectin (r=0.432, p<0.001) and vWf (r=0.349, p=0.001) but not with SBP (r=0.198, p=0.069). However, in multivariate analysis, only disease group (i.e. health, hypertension or stroke) was associated with increased CECs. Acute ischaemic stroke is associated with increased numbers of CECs. The latter correlate well with established plasma markers of endothelial dysfunction or damage, thus unequivocally confirming severe vasculopathy in this condition. However, the greatest influence on CECs numbers was clinical group.
Keywords: Endothelial damage; acute ischaemic stroke; hypertension; circulating endothelial cells; CD146